Integration of Kaili Local Culture in Learning the Theme of My Living Environment in Elementary Schools - Rizal, Rizal; Herlina, Herlina; Surahman, Surahman; Yunus, Sitti Rahma; Yaakob, Mohd Faiz Mohd (Program Magister Teknologi Pendidikan Universitas Jambi, 2025)
The purpose of this study is to describe local culture along with its content analysis as a source of learning on the theme of my living environment in grade IV of Elementary School. This study is a qualitative approach study and uses a phenomenological design. The subjects in this study were teachers, grade IV students of Elementary School 18 Banawa and community leaders in Banawa sub-district. The data acquisition techniques used were observation, interviews, literature studies and documentation. This study uses data analysis techniques, namely data reduction, data presentation and drawing conclusions. Based on the results of research conducted at Elementary School 18 Banawa, local culture in Banawa sub-district that can be used as a source of learning are the gonggati folklore, posisani songs and pusentase tourism. This is evidenced by the gonggati folklore, posisani songs and pusentase tourism which are local cultures that are still known by some people and are local cultures that have not been included in learning in grade IV, namely in theme 1, theme 5, theme 7, theme 8 and theme 9 making the local culture of Kaili in Banawa sub-district a source of learning that is expected to maintain local culture from generation to generation.